A clinical evaluation of the pharmacokinetics and pharmacodynamics of intravenous alfaxalone in cyclodextrin in male and female rats following a loading dose and constant rate infusion - White, Kate L.; Paine, Stuart; Harris, John (Wiley, 2017)
Objective: To characterise, as a clinical study, the pharmacokinetics and pharmacodynamics and describe the hypnotic effect of the neurosteroid alfaxalone (3α-hydroxy-5 α-pregnane-11, 20-dione) formulated with 2-hydroxypropyl-β-cyclodextrin in male and female rats. Study design: Prospective, experimental laboratory study. Animals: Twelve (six male and six female) adult, aged matched Sprague Dawley rats. Methods: Surgery and instrumentation was performed under isoflurane anaesthesia in an oxygen/nitrous oxide mixture (1:2) and local anaesthetic infiltration. All animals received a loading dose (1.67 mg kg -1 minute -1) for 2.5 minutes followed by a constant rate infusion (0.75 mg kg -1 minute -1) for 120 minutes of alfaxalone. Isoflurane and nitrous oxide was discontinued 2.5 minutes after the alfaxalone infusion started. Cardiorespiratory variables (heart rate, respiratory rate, arterial blood pressure, end tidal carbon dioxide tension) and clinical signs of anaesthetic depth were evaluated throughout anaesthesia. Carotid artery blood samples were collected at strategic time points for blood gas analysis, haematology and biochemistry and plasma concentrations of alfaxalone. Plasma samples were assayed using liquid chromatography-mass spectrometry (LC/MS). Results: There were significant differences between the sexes for plasma clearance (p = 0.0008), half-life (p = 0.0268) and mean residence time (p = 0.027). Mean arterial blood pressure was significantly higher in the male rats (p = 0.0255). Conclusions and clinical relevance: This study confirms alfaxalone solubilized in a 2-hydroxypropyl-β-cyclodextrin provides excellent total intravenous anaesthesia in rats. Sex-based differences in pharmacokinetics and pharmacodynamics were demonstrated and must be considered when designing biomedical research models using alfaxalone.